STRUCTURE AND HARDNESS CHARACTERISTICS OF 50Cr-50Al COATING PREPARED BY A MECHANICAL ALLOYING TECHNIQUE: EFFECTS OF HEAT TREATMENT TEMPERATURE - Sudiro, Toto; Sebayang, Perdamean (LIPI Press, 2015)
In the present work, a mechanical alloying technique was used to prepare 50Cr-50Al (in atomic, at %) coating on the surface of low carbon steel. The coated samples were then annealed in a vacuum at elevated temperatures of 600, 700, 800, and 900C for 2h, separately. The effects of annealing temperature on the structure characteristic of 50Cr-50Al coating were studied by XRD and SEM-EDX, and coating hardness was measured by micro-Vickers hardness test. The results showed that the annealing process led to the formation of inter-metallic phases and interdiffusion of Fe element from the substrate and Cr, Al elements from the coating, depending on annealing temperature. As annealing temperature increased to 900C, however, X-ray diffraction analysis indicated the formation of Al2O3. Meanwhile, the hardness of cross-sectional of coating increased after annealing at 600C. The coating hardness decreased as annealing temperatures increased.